2018
DOI: 10.1155/2018/5823870
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Urinary Markers for Detection of Upper Tract Urothelial Carcinoma: Is Upper Tract Urine More Accurate than Urine from the Bladder?

Abstract: Objectives To assess the performance of urine markers determined in urine samples from the bladder compared to samples collected from the upper urinary tract (UUT) for diagnosis of UUT urothelial carcinoma (UC). Patients and Methods The study comprised 758 urine samples either collected from the bladder (n = 373) or UUT (n = 385). All patients underwent urethrocystoscopy and UUT imaging or ureterorenoscopy. Cytology, fluorescence in situ hybridization (FISH), immunocytology (uCyt+), and nuclear matrix protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…However, due to potential cell damage, which is unavoidable when collecting upper urinary tract urine with a ureteral catheter, selective upper tract urinary cytology can occasionally show false positives. 11,17 Although we predicted an increase in the false positive rate due to catheter manipulation, as previously reported in NMP22, 18 the present study showed a false positive rate of 0%. This result indicated that 5-ALA-induced fluorescent selective upper tract urinary cytology was unaffected by catheterization.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, due to potential cell damage, which is unavoidable when collecting upper urinary tract urine with a ureteral catheter, selective upper tract urinary cytology can occasionally show false positives. 11,17 Although we predicted an increase in the false positive rate due to catheter manipulation, as previously reported in NMP22, 18 the present study showed a false positive rate of 0%. This result indicated that 5-ALA-induced fluorescent selective upper tract urinary cytology was unaffected by catheterization.…”
Section: Discussionsupporting
confidence: 80%
“…Selective upper tract urinary cytology obtained by washing is the gold standard tool for detecting UTUC. However, due to potential cell damage, which is unavoidable when collecting upper urinary tract urine with a ureteral catheter, selective upper tract urinary cytology can occasionally show false positives . Although we predicted an increase in the false positive rate due to catheter manipulation, as previously reported in NMP22, the present study showed a false positive rate of 0%.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations